3D Reconstruction and Intelligent Digital Conservation of Ancient Buildings Based on Laser Point Cloud Data. (27th May 2022) - Qiu, Yahui
Abstract : With the wide application of computer technology, how to carry out digital modeling and virtual simulation for the protection of ancient buildings has become a new research field. The combination of LiDAR (LiDAR) point cloud data can significantly improve the performance of 3D spatial information extraction of buildings. To improve the level of ancient building conservation, this article uses LiDAR point cloud data to collect ancient building data, extracts 3D spatial location information from multisource remote sensing optical stereo images, restores 3D spatial structure information of buildings from LiDAR point cloud data, conducts optimized topology research work, jointly extracts 3D spatial information of buildings with structural constraints, and compares the collected data with the original data. The research results show that the traditional data collection method has a large error of about 10%, while the data collected by LiDAR (LiDAR) point cloud data in this article is close to the original data. The error is around 3%, which can well complete the 3D reconstruction and protection of ancient buildings.